Decreased Event-Related Desynchronization of Mental Rotation Tasks in Young Tibetan Immigrants - Xiang, Zu-qiang; Huang, Yi-lin; Luo, Guang-li; Ma, Hai-lin; Zhang, De-long (Frontiers in Human Neuroscience, 2021)
The present study explored the event-related desynchronization (ERD) of the spatial manipulation in high-altitude immigrants through combining the mental rotation task and the electroencephalogram time-frequency analysis. The mental rotation response of immigrants who had lived in high-altitude area for three years was significantly slower than that of the low-altitude group. The time-frequency analysis showed that the ERD was decreased during mental rotation task within the time window (400-700 ms) in immigrants. The decreased ERD was observed at the parietal-occipital regions within the alpha band as well as at the central-parietal regions within the beta band in these immigrants. The decreased ERD might embody the motor cortical excitability in high-altitude immigrants from hypoxia, which provided insights into the neural mechanism of spatial cognition change from high-altitude exposure.